Automotive powertrain science and technology - Bonnick, Allan W. M. (2020)
"A motor vehicle's powertrain consists of the components which generate power and enable it to move - its engine, exhaust system, transmission, drive shaft, suspension and wheels. Any automotive engineering student going beyond basic mechanics will need a sound knowledge of the mathematics and scientific principles, particularly calculus and algebra, which underpin powertrain technology. This textbook supports a series of courses, for instance BTEC unit 28 "Further Mathematics for Engineering Technicians", which is a requisite for a foundation degree in automotive engineering, and BTEC higher unit 25 "Engine and Vehicle Design and Performance", without giving full coverage of automotive technology. It is a more focused companion to the author's Automotive Science & Mathematics 978-0-7506-8522-1, also published by Routledge"--
Includes bibliographical references and index.
Keywords: Automobiles -- Power trains -- Design and construction; Engineering mathematics